Common Somali Indigenous Chicken Breeds, in Mogadishu, Somalia: Indigenous Chicken Breeds - Abdi - Soojeede, Mohamed Ibrahim (Integrated Journal for Research in Arts and Humanities, 2022)
The main aim of this report is to determine the phenotypic characteristics of Somali indigenous chickens. This research is the initial stage toward a future initiative to differentiate and improve Somali local chicken breeds. There are several indigenous and exotic chicken breeds in Somalia, as well as many other hybrids of chicken; however, this study focused on indigenous breeds that differ in body form, colors, comb type, and capacity to adapt to a given environment in Somalia. The five main indigenous chicken breeds in Somalia. The first indigenous chicken (IC) is Dooro Tiyeglow (Tiyeglow chicken), they have well adapted mostly to agro-pastoral communities’ regions like Bakool region and it has a remarkable beard feather, it also has a single upright comb broad. The second (IC), is Qoordiir (Naked Neck chicken), which is indigenous chicken mostly they have some tassel in the front part of its neck. The prominent plumage color is white and red stripes or red with white strips. Third (IC), is Dooro Jarray (Somali short chicken), this chicken is part of an eco-friendly chicken and is well-known for its small body size. And the common feature of this chicken is black shanks or gray-black shanks. Fourth (IC) is Dooro Buuftoy (Ovambo chickens), this chicken is considered to be smaller in size than exotic chickens, yet it comes in black and red colors. This has a strong personality and is very aggressive. The Fifth (IC) is Dooro Sawahili (Swahili chicken) this chicken is an exotic species that interbreed many local chickens, comes from many angles, has a huge body frame, and is good in egg production. The recommendation of this study is to undertake a government policy to encourage the conservation of Somalia's indigenous chicken breeds in order to prevent extinction and to make development and improvement of local chickens.